(untitled) (Journal of Science and Engineering, 2026)
The seismic response of the structure with underground stories is observed with the consideration of soil structure interaction (SSI). The soil is replaced by springs assigned at the joints. The spring parameters are calculated from ASCE and contemporary literature. The study is conducted on three sets of building with three stories. Two input motions, i.e. Gorkha-Barpak (2015) earthquake time history and time history matched with response spectrum for medium soil from IS 1893 (Part 1): 2002 is used for the analysis. The response of the structure is compared in terms of the time period, roof displacement and shear force demand at ground floor level. The study reveals that on considering SSI, there is an increase in the lateral time period of the building, resulting in a decrease in shear force demand and an increase in lateral displacement. However, the change in the demand is observed to be low and would rarely alter the design of the structure.